PENGARUH DAYA TARIK IKLANTERHADAP NIAT BELI PRODUK FRESH CARE MELALUIBRAND IMAGE - NUZUL AZHAR, PHAZA (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: Companies are required in order to create a product that can compete with other products if it wants to survive in the current competitive business. One such competition in minyak angin product.One of them producer is a Fresh Care.Strategies promotion intense through advertising made Fresh care??famous in the community. So with promotion through the advertising appeal on television can create the brand image that formed memories in the minds of consumers and that can create the purchase intention.The purpose of this study is to examine and analyze influence the advertising appeal on purchase intention and brand image as intervening variables. This Samples taken as many as 165 people. Measuring instrument used was a questionnaire as data analysis with path analysis. The results showed that the advertising appeal influence on brand image, brand image influence on purchase intention, and the advertising appeal influence on purchase intention. Keywords:advertising appeal, brand image, purchase intention.